Workshop Kajian Fikih Munakahat Guna Meningkatkan Pemahaman Cara Meraih Keluarga Sakinah - Nasrulloh, Muhammad Farid; Fodhil, Muhammad; Mustafida, Livia; Nashoikh, Afif Kholisun; Wafa, Muhammad Aliyul; Sirojuddin, Didin (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2025)
Munakahat fiqh is a branch of jurisprudence that regulates various aspects related to marriage and husband and wife relationships in Islam. This concept is very important, considering that marriage is not just a social bond, but also a sacred agreement between two individuals which aims to build a family that is sakinah, mawaddah and rahmah. Society today is faced with various challenges that can disrupt household harmony. Economic factors, changes in social values, and the influence of technology are some of the main causes. Economic pressure often causes stress which can trigger conflict between husband and wife. Some of the problems that exist in Randuwatang Village regarding Munakahat Fiqh are that it is important to first understand the concept of the Sakinah family. The Sakinah family is a family that is in a state of harmony and peace, in accordance with Islamic teachings. The approach or method used is Service Learning (SL). The service learning method is an approach to teaching that combines academic objectives in an effort to raise awareness in solving problems directly. Based on the results and discussion of the Seminar "Study of Munakahat Jurisprudence in the Context of Achieving a Sakinah Family" which was held in Randuwatang Village, Kudu District, Jombang Regency, it can be concluded that the seminar held was successful in providing new knowledge about marriage law in Islam and the importance of building a sakinah family.